Contra-Equity Accounting for R&D. - Johnson, Orace (The Accounting Review, 1976)
This article cites a study evaluating the concepts concerning possible accounting solutions to the classification problem of research and development costs. This study, reportedly, is a continuation of a previous study that focuses on contra-equity accounting for research and development. In that study, the causal relation between research and development effort and benefit was defined operationally to be the coefficient of cross correlation between the ratio of research and development expense to total assets and the ratio of income to net worth. This article deals with conceptual foundations, procedural alternatives, the contra-equity proposal, hypotheses and evidence, and institutional matters. The original study treated amortization as if it started in the year of cost incurrence for all assumed lines. Thus, all three amortization patterns for one-year lives had coefficients identical with the coefficient for current expensing. The present replication extended the analysis by adding a one-year-lag alternative, with all amortization starting the year after cost incurrence. The present study also added one new relationship to test the capital loss alternative.